Characterization of oxidation and reduction of a Palladium-Rhodium alloy by atom-probe tomography - Li, T; Bagot, P; Smith, G; Marquis, E; Tsang, S (2012)
Platinum group metals (PGMs) are used in numerous catalyst applications, including conversion of engine exhaust gases and hydrocarbon reforming. Reducing the loading of PGMs without diminishing the overall catalyst activity is a major challenge. Fundamental studies of PGMs under reactive conditions can assist the design/synthesis of "nanoengineered" catalysts, tunable and optimized for cost, stability, and performance. In the present study, the oxidation and reduction behavior of a Pd-6.4 at. % Rh alloy is investigated following treatment at 873 K for various exposure times using atom-probe tomography. For short oxidation times (10 min), an oxide layer with PdO stoichiometry grows on the surface. As the oxidation time increases, two phases with stoichiometries of (Rh Pd )O and (Pd O) evolve. When the alloy is subsequently reduced in hydrogen, a nanoscale dispersion of Rh-rich metallic regions remains. This provides a route for the synthesis of multifunctional catalysts with different nanosurface regions in close proximity to one another. © 2012 American Chemical Society.